The Impact Of Climate Change On Food Security Political Economy Perspective - Fuzy Firda Zhan; Syarif Redha Fachmi Al Qadrie; Ratu Zahirah Lutfie; Dwita Suci Rochima; Syarifah Nurma Afhiani (International Journal of Business and Quality Research, 2023)
This paper aims to analyze the Impact of Climate Change on Food Security from a Political Economy Perspective. In the last few decades, the issue of climate change has received increasing global attention and is considered one of the most serious and urgent environmental issues that need to be addressed by the international community, and Indonesia is no exception. This climate crisis has had various impacts, one of which is on food security for the community, the number of crop failures to disasters due to the climate crisis resulting in food supplies that are not smooth, causing other domino impacts such as hunger, poverty and the economy. By using qualitative research methods. The qualitative method was chosen based on the conditions and situation of the research object and the expected results after the research.